2022-RA-1303-ESGO Analysis of hospitalization of patients with malignant vulvar diseases operated between 02.2020 and 04. 2022 in the department of oncological gynecology of the centre of oncology, opole, poland. (20th October 2022) - Kalus, Marcin; Nowak, Krzysztof; Mrugala, Maja; Borowiec, Zofia; Milnerowicz-Nabzdyk, Ewa
Abstract : Introduction/Background: The objective: the analysis of patients with V-Y technique vulvar reconstruction in the treatment of malignant vulvar diseases between 02.2020 and 04. 2022 in the Department of Oncological Gynecology Methodology: The surgical treatment was performed in 25 patients: 21 with squamous cell carcinoma and 4 with vulvar Paget disease. 18 women underwent complete radical vulvectomy and 7 partial radical vulvectomy (hemivulvectomy or wide tumor resection). In the group with complete radical vulvectomy 6 patients were qualified to the V-Y technique vulvar reconstruction. In 12 patients the systemic inguinal lymphadenectomy (uni- or bilateral) was performed, of which 5 was diagnosed with node metastases. In 4 patients the SLN procedure was performed, with positive results (lymph node metastases) in 2 patients. 2 patients after the simultaneous reconstruction group required secondary wound suturing in the postoperative period. In the group of patients after partial or complete radical vulvectomy without the reconstruction 6 patients needed secondary surgical intervention. Results: The average operating time without the simultaneous reconstruction was 160 min. and with the reconstruction was 205 min. The average healing time without the reconstruction was 30 days and with the reconstruction 23 days. The mean satisfaction index without the reconstruction was 6/10 and with the reconstruction 8/10. Conclusion: 1. The surgical procedures in the vulvar malignant diseases with simultaneous reconstruction are more time-consuming but more effective for the patient's quality of life than the procedures without reconstruction. 2. Secondary wound suturing in the postoperative period had no impact on the patient's final treatment assessment. 3. The number of patients treated with reconstructive procedures is an obvious limitation of this analysis, but it should be considered as a pilot study. The number of patients enrolled will be growing and more detailed meta-analysis is planned for the following years.